Spatial Analysis in The Process of Housing Development: Use and Role of 3D Measurement Technology Through The Case of Prey Veng Province, Cambodia - Goto, Katsushi; Shimazaki, Hikaru; Tanaka, Tomoaki (MAJ - Malaysia Architectural Journal, 2025)
In the realm of housing development, particularly within informal settlements, spatial analysis is a crucial tool for engaging residents and multiple stakeholders. It extends beyond merely providing technical input to built environment professionals such as planners and architects. With the advent of the ‘Digital Twin’ technology over the last decade, acquiring spatial and 3D data of the built environment has become more affordable and diverse. This paper explores the relevance and potential of 3D measurement technologies in the development of informal settlements, focusing on a case study from Neak Loeung, Prey Veng Province, on the outskirts of Phnom Penh, Cambodia. The research involved conducting 3D measurements at the Neak Loeung housing development site and acquiring detailed 3D data of the area. While addressing the challenges associated with these measurement methods, the study also examines the use of 3D data in early-stage housing development processes such as community networking and strategic incremental planning. Moreover, the paper discusses the broader challenges related to the technological limitations in accessing and operating visual information, as well as the role of 3D data in the learning and skill development of both community members and professionals, with a particular focus on young community architects.